The EU Eastern Enlargement from today's perspective - Ionelia Bianca Bosoancă (CES Working Papers, 2021)
This paper discusses the major challenges for the present European Commission, starting with Brexit and ending with issues such as EU Eastern Enlargement from today's perspectives, trying to explain why it is difficult to talk about enlargement in a fragmented European Union. How will the European Neighborhood Policy and Enlargement Negotiations evolve in the actual mandate of the European Commission? Did the European Commission succeed in offering Eastern states the opportunity to join the European Union by developing instruments encouraging states to meet the accession criteria? A qualitative analysis will be used to highlight the novelty elements analyzed by the proposed theme; the author uses a study case using as research instruments discourse and content analysis. Therefore, the main objective of this research paper is to highlight how the European leaders' discourse on a possible enlargement of the European Union has evolved.
Keywords: 330; European Union; European Neighborhood Policy; challenges; enlargement; perspectives